To hell and back : Europe, 1914-1949 - Kershaw, Ian (2015)
Introduction: Europe's era of self-destruction – On the brink – The great disaster – Turbulent peace – Dancing on the volcano – Gathering shadows – Danger zone – Towards the abyss – Hell on earth – Quiet transitions in the dark decades – Out of the ashes